Stress distribution and fracture resistance of green reprocessed polyetheretherketone (PEEK) single implant crown restorations compared to unreprocessed PEEK and Zirconia: an in-vitro study - Marwa Emam; Ahmed Mohamed Arafa (BMC, 2023)
Abstract Background It is unclear which crown materials are optimum to disperse the generated stresses around dental implants. The objective of this study is to assess stress distribution and fracture resistance of green reprocessed Polyetheretherketone (PEEK) in comparison to un-reprocessed PEEK and zirconia single implant crown restorations. Methods Twenty crowns (n = 20) were obtained, five from zirconia and fifteen from pressed PEEK that were subdivided into 3 groups of five specimens each (n = 5) according to weight% of reprocessed material used. A 100% new PEEK was used for the first group, 50% new and 50% reprocessed PEEK were used for the second group, and a 100% reprocessed PEEK was used for the third group. Epoxy resin model with dental implant in the second mandibular premolar was constructed with strain gauges located mesially and distally to the implant to record strain while a load of 100 N was applied with 0.5 mm/min then specimens of all groups were vertically loaded till failure in a universal testing machine at cross head speed 1 mm/min. Data was statistically analyzed by using One-way Analysis of Variance (ANOVA) followed by Post-hoc test when ANOVA test is significant. Results No significant difference between strain values of tested groups (p = 0.174) was noticed. However, a significant difference between fracture resistance values was noticed where the zirconia group recorded a significantly higher value (p < 0.001). Conclusions Implant restorative materials with different moduli of elasticity have similar effects regarding stresses distributed through dental implant and their surrounding bone. Reprocessed PEEK implant restorations transmit similar stresses to dental implant and surrounding bone as non-reprocessed PEEK and zirconia restorations. Zirconia failed at higher load values than all tested PEEK restorations but all can be safely used in the posterior area as crown restorations for single implants. Clinical relevance Applying "green dentistry" principles may extend to include reprocessing of pressed PEEK restorative materials without affecting the material's shock absorption properties.